Chemical freeze-out curve in heavy-ion collisions and the QCD critical point - Lysenko, Artemiy; Gorenstein, Mark; Poberezhniuk, Roman; Vovchenko, Volodymyr (Physical Review C, 2025)
The chemical freeze-out curve in heavy-ion collisions is investigated in the context of a quantum chromodynamics (QCD) critical point (CP) search at finite baryon densities. Taking the hadron resonance gas picture at face value, chemical freeze-out points at a given baryochemical potential provide a lower bound on the possible temperature of the QCD CP. We first verify that the freeze-out data in heavy-ion collisions are well described by a constant energy per particle curve, 𝐸/𝑁=const, under strangeness neutrality conditions (𝜇𝑆≠0, 𝜇𝑄≠0). We then evaluate the hypothetical lower bound on the freeze-out curve based on this criterion in the absence of strangeness neutrality (𝜇𝑆=0, 𝜇𝑄=0) and confront it with recent predictions on the CP location. We find that recent estimates based on Yang-Lee edge singularities from lattice QCD data on coarse lattices (𝑁𝜏=6) place the CP significantly below the freeze-out curve, hinting at the importance of performing continuum extrapolation within this method. Predictions based on functional methods and holography place the CP slightly above the freeze-out curve, indicating that the QCD CP may be located very close to the chemical freeze-out in 𝐴+𝐴 collisions at √𝑠𝑁⁢𝑁=3.5−6GeV.